Advancing Sustainability Education through Narrative Digital Media: A Structural Model of Student Acceptance - Deli Deli; William William; Clara Audelia; Bayu Syahputra (Universitas Hamzanwadi, 2026)
While teaching the 17 Sustainable Development Goals (SDGs) is important, many schools struggle to keep students interested, often leading to boredom or confusion. This research evaluates a 2D visual novel, Liora Island, for enhancing engagement and reducing cognitive complexity when teaching the SDGs. Using a quantitative associative design and the Technology Acceptance Model (TAM), five variables Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Using (ATU), Behavioral Intention (BI), and Actual Use (AU) were examined among 139 students at Mondial Senior High School, Batam. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings reveal high student acceptance across all TAM constructs. Perceived ease of use emerged as the primary driver of adoption, strongly influencing perceived usefulness and attitude. Attitude toward using significantly predicted behavioral intention, which in turn strongly determined actual use. Perceived usefulness showed smaller but significant effects on attitude and behavioral intention, indicating that usability outweighs instructional value during initial acceptance. This study contributes to sustainability pedagogy by identifying usability as key in reducing